The Winter Stoneflies (Plecoptera: Capniidae) of Mississippi - Nations, Tina M. (Illiesia, 2007)
The Mississippi winter stonefly fauna includes seven Allocapnia species A. aurora Ricker, A. granulata (Claassen), A. mystica Frison, A. polemistis Ross & Ricker, A. rickeri Frison, A. starki Kondratieff & Kirchner and A. virginiana Frison and Nemocapnia carolina Banks; Allocapnia recta (Claassen),previously recorded from the state, is deleted from the list and all records for this species are assigned to A. starki. The male epiproct and 8th tergal process of the Mississippi Capniidae were examined with scanning electron microscopy, and the female subgenital plates were also studied to determine if these could be reliably separated. A brief description is given for female genital segments of A. polemistis.
Keywords: entomologija; Plecoptera; insekti; vrbnice; Mississippi; United States of America; ZDA